Ação rescisória por divergência jurisprudencial - Fidalgo, Alexandre (2013)
This study aims to discuss the possibility of rescissory action based on article 485, V, of the Code of Civil Procedure, under the justification of jurisprudential divergence. It defends that the merit decision transited in rem judicatam may be rescinded if it is contrary to prevailing jurisprudence at the time, considering analogous situations and incurred in a similar historical and social moment, under penalty of offense to the principle of isonomy, not applicable the Supreme Court Precedent Nr. 343 as being unconstitutional. Under the same argument, it presents the possibility of rescissory action against decision that does not obey the binding precedent and decision contrary to prevailing jurisprudence determined later. It also defends the possibility of rescissory action against sentence based on rule of law later declared unconstitutional and against decision declaring unconstitutional rule of law later declared constitutional. The study is presented in three main parts. The first one relates to the concepts and legal nature of the rescissory action, its admissibility presuppositions and the traditional assumptions of rescissory action. The second part addresses the issue of the possibility of rescissory action based on jurisprudential divergence. Finally; the third part is dedicated to the concepts of the rescissory action elements (parties, cause of action and claim - ius rescindens and ius rescissorium), as well as it address the jurisdiction and the suspension of effects of the rescinded decision